Penerapan Teknologi Mesin Penepung dan Pemasaran Digital untuk Meningkatkan Produktivitas dan Daya Jual Produk UMKM Kelompok Usaha Tepung Mocaf di Desa Majalangu, Watukumpul: Application of Flour Machine Technology and Digital Marketing to Increase Productivity and Marketability of MSME Products of the Mocaf Flour Business Group in Majalangu Village, Watukumpul - Saputra, Eqwar; Ma’ruf, Anwar; Fauziridwan, Meydy (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This service aims to apply production technology in the form of flouring machines and provide digital marketing training to increase productivity, quality, and selling power of MSME products from the Mocaf Flour Business Group in Majalangu Village, Watukumpul, Pemalang. Through this activity, it is hoped that it can help Davia Watukumpul’s mocaf flour production process to be more optimal. Apart from implementing machines, digital marketing training is provided to partners to support marketing activities and increase product selling power. This service activity begins with several stages including planning, preparation, implementation, activity evaluation, and mentoring. 17 service participants took part in this activity, consisting of 10 men and 7 women. Participants are trained on how to operate tools, in the form of penpung tools. The training process that has been carried out shows that participants have increased their knowledge and understanding. The percentage of participants’ knowledge increased by 60%. This shows that the participants paid attention to what the presenter had explained. Through this training, it is hoped that participants will become more enthusiastic in promoting products that have been created on social media or e-commerce according to what has been taught.